Early Recurrence of First Unprovoked Seizures in Children. (28th November 2017) - Goldberg, Leah R.; Kernie, Catherine G.; Lillis, Kathleen; Bennett, Jonathan; Conners, Gregory; Macias, Charles G.; Callahan, James; Akman, Cigdem; Allen Hauser, W.; Kuppermann, Nathan; Dayan, Peter S.
Abstract: Objectives: The risk of early seizure recurrences after first unprovoked seizures in children is largely unknown. We aimed to determine the rate of seizure recurrence within 14 days of first unprovoked seizures in children and identify associated risk factors. Secondarily, we aimed to determine the risk of recurrence at 48 hours and 4 months. Methods: We conducted a secondary analysis of a multicenter cohort study of children 29 days to 18 years with first unprovoked seizures. Emergency department (ED) clinicians completed standardized histories and physical examinations. The primary outcome, recurrent seizure at 14 days, and the secondary outcomes, recurrence at 48 hours and 4 months, were assessed by telephone follow‐up and medical record review. For each recurrence time point, we excluded those patients for whom no seizure had recurred but chronic antiepileptic drugs had been initiated. Results: A total of 475 patients were enrolled in the parent study. Of evaluable patients for this secondary analysis, 26 of 392 (6.6%, 95% confidence interval [CI] = 4.4%–9.6%) had recurrences within 48 hours of the incident seizures, 58 of 366 (15.8%, 95% CI = 12.3%–20.0%) had recurrences within 14 days, and 107 of 340 (31.5%, 95% CI = 26.6%–36.7%) had recurrences within 4 months. On logistic regression analysis, age younger than 3 years was independently associated with a higher risk of 14‐day recurrence (adjusted odds ratio [OR] = 2.1, 95% CI = 1.2–3.7; p = 0.01). Having had more than one seizure within the 24 hours prior to ED presentation was independently associated with a higher risk of seizure recurrence at 48 hours (adjusted OR = 4.3, 95% CI = 1.9–9.8; p < 0.001). Conclusions: Risk of seizure recurrence 14 days after first unprovoked seizures in children is substantial, with younger children at higher risk. Prompt completion of an electroencephalogram and evaluation by a neurologist is appropriate for these children.